A predictive model of polymetastatic disease from a multicenter large retrospectIve database on colorectal lung metastases treated with stereotactic ablative radiotherapy: The RED LaIT-SABR study. (March 2023) - Nicosia, Luca; Franceschini, Davide; Perrone-Congedi, Francesca; Molinari, Alessandro; Gerardi, Marianna Alessandra; Rigo, Michele; Mazzola, Rosario; Perna, Marco; Scotti, Vieri; Fodor, Andrei; Iurato, Aurelia; Pasqualetti, Francesco; et al.
Highlights: We developed a model of polymetastatic progression of colorectal cancer (CRC). Data from the multicenter LaIT-SABR study were used in this secondary analysis. Oligometastases number and total tumor volume were combined to stratify population. We identified 3 risk classes of polymetastatic progression after SABR. This model can be used to personalize SABR prescription in oligometastatic CRC. Abstract: Aim: Stereotactic ablative radiotherapy (SABR) showed increasing survival in oligometastatic patients. Few studies actually depicted oligometastatic disease (OMD) evolution and which patient will remain disease-free and which will rapidly develop a polymetastatic disease (PMD) after SABR. Therefore, apart from the number of active metastases, there are no clues on which proven factor should be considered for prescribing local treatment in OMD. The study aims to identify predictive factors of polymetastatic evolution in lung oligometastatic colorectal cancer patients. Methods: This international Ethical Committee approved trial (Prot. Negrar 2019-ZT) involved 23 Centers and 450 lung oligometastatic patients. Primary end-point was time to the polymetastatic conversion (tPMC). Additionally, oligometastases number and cumulative gross tumor volume (cumGTV) were used as combined predictive factors of tPMC. Oligometastases number was stratified as 1, 2–3, and 4–5; cumGTV was dichotomized to the value of 10 cc. Results: The median tPMC in the overall population was 26 months. Population was classified in the following tPMC risk classes: low-risk (1–3 oligometastases and cumGTV ≤ 10 cc) with median tPMC of 35.1 months; intermediate-risk (1–3 oligometastases and cumGTV > 10 cc), with median tPMC of 13.9 months, and high-risk (4–5 oligometastases, any cumGTV) with median tPMC of 9.4 months (p = 0.000). Conclusion: The present study identified predictive factors of polymetastatic evolution after SABR in lung oligometastatic colorectal cancer. The results demonstrated that the sole metastases number is not sufficient to define the OMD since patients defined oligometastatic from a numerical point of view might rapidly progress to PMD when the cumulative tumor volume is high. A tailored approach in SABR prescription should be pursued considering the expected disease evolution after SABR, with the aim to avoid unnecessary treatment and toxicity in those at high risk of polymetastatic spread, and maximize local treatment in those with a favorable disease evolution.